Functional expression of the GABAA receptor α2 and α3 subunits at synapses between intercalated medial paracapsular neurons of mouse amygdala - Geracitano, Raffaella; Fischer, David T.; Kasugai, Yu; Ferraguti, Francesco; Capogna, Marco (Frontiers in Neural Circuits, 2012)
In the amygdala, GABAergic neurons in the intercalated medial paracapsular cluster (Imp) have been suggested to play a key role in fear learning and extinction. These neurons project to the central (CE) amygdaloid nucleus and to other areas within and outside the amygdala. In addition, they give rise to local collaterals that innervate other neurons in the Imp. Several drugs, including benzodiazepines (BZ), are allosteric modulators of GABAA receptors. BZ has both anxiolytic and sedative actions, which are mediated through GABAA receptors containing α2/α3 and α1 subunits, respectively. To establish whether α1 or α2/α3 subunits are expressed at Imp cell synapses, we used paired recordings of anatomically identified Imp neurons and high resolution immunocytochemistry in the mouse. We observed that a selective α3 subunit agonist, TP003 (100 nM), significantly increased the decay time constant of the unitary IPSCs. A similar effect was also induced by zolpidem (10 μM) or by diazepam (1 μM). In contrast, lower doses of zolpidem (0.1–1 μM) did not significantly alter the kinetics of the unitary IPSCs. Accordingly, immunocytochemical experiments established that the α2 and α3, but not the α1 subunits of the GABAA receptors, were present at Imp cell synapses of the mouse amygdala. These results define, for the first time, some of the functional GABAA receptor subunits expressed at synapses of Imp cells. The data also provide an additional rationale to prompt the search of GABAA receptor α3 selective ligands as improved anxiolytic drugs.